Constitutionality of Regional Head Election Campaigns on Campus Based on Constitutional Court Decision Number 69/PUU-XXII/2024 - Rohmah, Elva Imeldatur (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
The Constitutional Court Decision Number 69/PUU-XXII/2024 marks a significant shift in Indonesia's electoral democracy landscape by allowing regional election campaigns to be conducted on university campuses, provided certain conditions are met. This decision has sparked new discourse concerning academic freedom, students' political rights, and the principle of institutional neutrality in higher education. This study aims to examine the constitutionality of regional election campaigns on campus based on the Constitutional Court Decision Number 69/PUU-XXII/2024, while also analyzing the practical challenges of its implementation. Using a normative juridical method with statutory and conceptual approaches, the study finds that the Court acknowledges the constitutional rights of the academic community to access political education and actively participate in democratic processes. However, the potential for unequal campaign access, concerns over campus neutrality, and the absence of detailed technical regulations pose serious implementation challenges. Furthermore, the principle of academic neutrality must be upheld to ensure that higher education institutions remain spaces for scholarly dialogue, not arenas for political contestation. Therefore, it is recommended that the General Elections Commission (KPU) and higher education institutions promptly formulate technical guidelines for on-campus campaigning to safeguard equality, neutrality, and academic integrity. Additionally, the role of students as agents of deliberative democracy should be strengthened through political literacy and open dialogue grounded in academic values